2015
DOI: 10.1292/jvms.14-0200
|View full text |Cite
|
Sign up to set email alerts
|

Sedative effects of intramuscular alfaxalone administered to cats

Abstract: The sedative effects of intramuscular (IM) alfaxalone in 2-hydroxypropyl-beta-cyclodextrin (alfaxalone-HPCD) were evaluated in cats. The cats were treated with alfaxalone-HPCD in five occasions with a minimum 14-day interval between treatments: an IM injection of 1.0 mg/kg (IM1), 2.5 mg/kg (IM2.5), 5 mg/kg (IM5) or 10 mg/kg (IM10), or an intravenous injection of 5 mg/kg (IV5). The sedative effects were evaluated subjectively using a composite measurement scoring system (a maximum score of 16). Cardio-respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 30 publications
2
57
0
1
Order By: Relevance
“…With respect to the cardiovascular function, it is worth to consider that a more comprehensive evaluation of the latter would imply at least the monitoring of the arterial blood pressure. Previous studies conducted in cats and dogs have shown that doses of alfaxalone higher than 5 mg kg -1 caused cardiovascular depression characterised by decreased mean arterial pressure in the absence of changes in the heart rate (Tamura et al 2015a;Tamura et al 2015b). Unfortunately, monitoring of systemic arterial blood pressure was not performed in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
See 1 more Smart Citation
“…With respect to the cardiovascular function, it is worth to consider that a more comprehensive evaluation of the latter would imply at least the monitoring of the arterial blood pressure. Previous studies conducted in cats and dogs have shown that doses of alfaxalone higher than 5 mg kg -1 caused cardiovascular depression characterised by decreased mean arterial pressure in the absence of changes in the heart rate (Tamura et al 2015a;Tamura et al 2015b). Unfortunately, monitoring of systemic arterial blood pressure was not performed in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Increasing the dose of IM alfaxalone would also increase the risk for cardiorespiratory side effects, as has been demonstrated in dogs, cats and rabbits (Huynh et al 2015;Tamura et al 2015a;Tamura et al 2015b). Moreover, because alfaxalone is only available in Europe at a concentration of 10 mg mL -1 doses higher than 5 mg kg -1 would result in unacceptably high IM injection volumes for small rodents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Two-week washout period is usually considered to be sufficient and many other alfaxalone studies use 2 weeks washout period. 15 The treatments were not randomised, but were administered in the following order: (a) treatment Meiji Seika Pharma Co., Ltd) and butorphanol (0.3 mg kg −1 ; Meiji Seika Pharma Co., Ltd); and (d) treatment AMB-Ati (see below). All drugs were administered IM.…”
Section: Methodsmentioning
confidence: 99%
“…De afwezigheid van een IV toegang in de huidige casus leidde ertoe dat een klassiek anesthetisch plan van premedicatie voorafgaand aan inductie moest aangepast worden naar een onmiddellijke inductie van de anesthesie via een IM toediening van alfaxalone. In een onderzoek van Tamura et al (2015) werden de sedatieve effecten van IM injectie van alfaxalone onderzocht zonder premedicatie, waarbij gezien werd dat de stof dosisafhankelijke sedatieve effecten teweegbrengt die acceptabel zijn vanaf 2,5 tot 10 mg/kg. Rodrigo-Mocholì et al (2016) toonden aan dat een solo-injectie van 5 mg/ kg alfaxalone IM een diepe sedatie teweegbrengt, een dosis en een toedieningswijze die in deze casus zelfs voor inductie van de anesthesie zorgden, aangezien de plaatsing van een LM mogelijk was na deze dosis.…”
Section: Inductiedosisunclassified